The influence of future changes in springtime Arctic ozone on stratospheric and surface climate - G. Chiodo; M. Friedel; S. Seeber; D. Domeisen; D. Domeisen; A. Stenke; A. Stenke; A. Stenke; T. Sukhodolov; T. Sukhodolov; F. Zilker; F. Zilker (Atmospheric Chemistry and Physics, 2023)
Stratospheric ozone is expected to recover by the mid-century due to the success of the Montreal Protocol in regulating the emission of ozone-depleting substances (ODSs). In the Arctic, ozone abundances are projected to surpass historical levels due to the combined effect of decreasing ODSs and elevated greenhouse gases (GHGs). While long-term changes in stratospheric ozone have been shown to be a major driver of future surface climate in the Southern Hemisphere during summertime, the dynamical and climatic impacts of elevated ozone levels in the Arctic have not been investigated. In this study, we use two chemistry climate models (the SOlar Climate Ozone Links – Max Planck Ocean Model (SOCOL-MPIOM) and the Community Earth System Model – Whole Atmosphere Community Climate Model (CESM-WACCM)) to assess the climatic impacts of future changes in Arctic ozone on stratospheric dynamics and surface climate in the Northern Hemisphere (NH) during the 21st century. Under the high-emission scenario (RCP8.5) examined in this work, Arctic ozone returns to pre-industrial levels by the middle of the century. Thereby, the increase in Arctic ozone in this scenario warms the lower Arctic stratosphere; reduces the strength of the polar vortex, advancing its breakdown; and weakens the Brewer–Dobson circulation. The ozone-induced changes in springtime generally oppose the effects of GHGs on the polar vortex. In the troposphere, future changes in Arctic ozone induce a negative phase of the Arctic Oscillation, pushing the jet equatorward over the North Atlantic. These impacts of future ozone changes on NH surface climate are smaller than the effects of GHGs, but they are remarkably robust among the two models employed in this study, canceling out a portion of the GHG effects (up to 20 % over the Arctic). In the stratosphere, Arctic ozone changes cancel out a much larger fraction of the GHG-induced signal (up to 50 %–100 %), resulting in no overall change in the projected springtime stratospheric northern annular mode and a reduction in the GHG-induced delay of vortex breakdown of around 15 d. Taken together, our results indicate that future changes in Arctic ozone actively shape the projected changes in the stratospheric circulation and their coupling to the troposphere, thereby playing an important and previously unrecognized role as a driver of the large-scale atmospheric circulation response to climate change.